Implementasi Konsep Thuma'ninah Sebagai Upaya Mengelola Kecemasan Pada Pandemi Covid-19 (Analisis Pemikiran Ibnu Qayyim Al-Jauziyah) - Arrasyid, Arrasyid (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aims to explain and analyze the concept of thuma'ninah Ibnu Qayyim al-Jauziyah as an effort to manage the anxiety that occurs in the Covid-19 pandemic. This research is qualitative research with a character study approach and uses exploratory, interpretation, and analysis methods. This study found data that the implementation of the thuma'ninah concept of Ibnu Qayyim al-Jauziyah as an effort to manage the anxiety that occurred during the Covid-19 pandemic, namely; first, implementing his understanding of the book of Allah Allah. Second, implementing the asthma of Allah regarding asy-Syukur. Third, implementing an understanding of the test is a form of Allah's love for His servants. By implementing these 3 (three) understandings, the anxiety felt by humans in the Covid-19 pandemic will be managed properly.